2017
DOI: 10.1111/jph.12602
|View full text |Cite
|
Sign up to set email alerts
|

Alternative products for Pratylenchus brachyurus and Meloidogyne javanica management in soya bean plants

Abstract: Nematodes stand out among the main soya bean yield limiting factors due to limitations in the main control methods, mainly when they are applied alone. Given the need of finding new control techniques, the aim of this study was to assess the efficiency of products based on biological control agents and on nutrients or products showing potential to induce resistance for Pratylenchus brachyurus and Meloidogyne javanica control in soya bean plants. The experiments were conducted in a greenhouse; nine treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
3
26
0
1
Order By: Relevance
“…The major drawback of using bionematicides is that they affect non-target, beneficial organisms that could serve as biological control agents in sustainable agriculture (Korthals et al, 2014). A study in Florida illustrated the impact of applying organic amendments and reported the difficulty in maintaining one beneficial group of organisms in a particular soil (McSorley, 2011). EPN constitutes such economically important biological control organisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major drawback of using bionematicides is that they affect non-target, beneficial organisms that could serve as biological control agents in sustainable agriculture (Korthals et al, 2014). A study in Florida illustrated the impact of applying organic amendments and reported the difficulty in maintaining one beneficial group of organisms in a particular soil (McSorley, 2011). EPN constitutes such economically important biological control organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of food security for an ever increasing global population, nematodes pose serious threat to agricultural crops worldwide (Miamoto et al, 2017). There are nearly 4,100 species of plant parasitic nematodes (PPN) reported to date that are currently a serious constraint for global food security (Jaouannet et al, 2013) causing yield loss of about 30% in susceptible crop varieties annually (tomatoes, eggplant, and melons) (Padgham et al, 2004;Collange et al, 2011). Among these root-knot nematodes (RKN) are widely spread and highly damaging (Zakaria et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the manufacturer, the moss product is composed of nutrients such as copper and zinc, the direct effect on root‐knot nematodes of which was previously reported (Rumiani, Karegar, Hamzehzarghani, & Banihashemi, ; Shaukat & Siddiqui, ). Recently, another zinc–sulphur–copper‐based product (Agro‐Mos) was applied to the shoots of soya bean plants and reduced the number of P. brachyurus and M. javanica /g of root (Miamoto, Rodrigues, Puerari, & Dias‐Arieira, ). Such an effect was attributed to the possibility that the product induced plant resistance to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The organic carbon found in Biozyme TF ® can also help to control the nematodes (El-Nagdi & Fattah, 2011), since it can influence the activity of these organisms in the soil or change the microbial population (Feng et al, 2003). Miamoto et al (2017) conducted a research with nutrientrich products and found similar results about the control of M. javanica and P. brachyurus in soybean, mainly when they were associated with the biological control performed with Trichoderma or Bacillus. Table 3.…”
Section: Nematode Penetration In the Root Systemmentioning
confidence: 99%